2020
DOI: 10.1002/jper.19-0385
|View full text |Cite
|
Sign up to set email alerts
|

Bisphosphonate‐induced reactive oxygen species inhibit proliferation and migration of oral fibroblasts: A pathogenesis of bisphosphonate‐related osteonecrosis of the jaw

Abstract: BackgroundThe onset mechanism for bisphosphonate‐related osteonecrosis of the jaw (BRONJ) has been reported, with a focus on bone remodeling, biofilm formation, and epithelial cell proliferation and migration. However, the involvement of stromal cells, especially fibroblasts, in the oral cavity is unclear. Therefore, this study was focused on how bisphosphonates (BPs) affect orthotopic periodontal ligament fibroblasts from the viewpoint of oxidative stress compared with ectopically obtained fibroblasts.Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 26 publications
2
29
0
3
Order By: Relevance
“…Starting with a study by Bagan et al [ 45 ] in 2014, which reported that oxidative stress was detected in the MRONJ patients, animal experiments and clinical studies focusing on oxidative stress as a pathophysiological mechanism of MRONJ have been actively conducted in recent years. It is noteworthy that oxidative stress and bisphosphonate may induce osteonecrosis of the jaw after an invasive dentoalveolar surgery in mice [ 46 ] and that bisphosphonate-induced ROS could delay wound healing by preventing the growth and migration of oral fibroblasts [ 47 ]. Besides, it is interesting that hypotaurine, which acts as an antioxidant associated with cellular defense against oxidative stress, was significantly elevated in patients’ saliva with MRONJ and thus showed potential as a new biomarker for the early detection of MRONJ [ 48 ].…”
Section: Staging and Possible Hypothesis Of The Pathogenesis Of Mronjmentioning
confidence: 99%
“…Starting with a study by Bagan et al [ 45 ] in 2014, which reported that oxidative stress was detected in the MRONJ patients, animal experiments and clinical studies focusing on oxidative stress as a pathophysiological mechanism of MRONJ have been actively conducted in recent years. It is noteworthy that oxidative stress and bisphosphonate may induce osteonecrosis of the jaw after an invasive dentoalveolar surgery in mice [ 46 ] and that bisphosphonate-induced ROS could delay wound healing by preventing the growth and migration of oral fibroblasts [ 47 ]. Besides, it is interesting that hypotaurine, which acts as an antioxidant associated with cellular defense against oxidative stress, was significantly elevated in patients’ saliva with MRONJ and thus showed potential as a new biomarker for the early detection of MRONJ [ 48 ].…”
Section: Staging and Possible Hypothesis Of The Pathogenesis Of Mronjmentioning
confidence: 99%
“…43 BPs increase apoptosis and decrease proliferation in a number of cell types in vitro. 12,13 In addition, the administration of zoledronic acid to oral gingival fibroblasts in vitro has been found to reduce the expression of extracellular matrix (ECM) proteins, including collagens I, II and III. 44 It has been shown that impairment of TGF-β1 signalling is related to oral mucosal soft tissue repair in BRONJ.…”
Section: Angiogenesismentioning
confidence: 99%
“…11 A recent report suggested that BPs can induce the production of reactive oxygen species, which inhibit the proliferation and migration of oral fibroblasts, thereby contributing to the pathogenesis of BRONJ. 12 Li et al 13 found that cell proliferation, adhesion, migration and osteogenic differentiation of periodontal ligament stem cells decreased significantly as a result of BRONJ lesions, a factor possibly important in the underlying mechanisms of BRONJ.…”
Section: Introductionmentioning
confidence: 99%
“…Gingival mesenchymal stem cells (GMSCs) are a group of stem cells isolated from the gingival lamina propria, and perform remarkable tissue regenerative potential and noteworthy immunomodulatory properties (8). Previous studies have showed that BPs inhibited healthy GMSCs viability and brogenesis in vitro (5,(9)(10)(11), however, there is a lack of direct evidence demonstrating the regeneration capacity of oral mucosa in BRONJ patients.…”
Section: Introductionmentioning
confidence: 99%